Use of Peripherally Inserted Central Catheter is integral to supportive care in Hematopoietic Stem Cells Transplantation – A single centre study - Sapkota, Sulav; Badarkhe, Girish V; Sannur, Raju; Priyadarshini, Mona; Naik, Radheshyam (Eastern Journal of Medical Sciences, 2019)
Background: Peripherally inserted central catheters (PICCs) are commonly being used in haematological diseases for treatment and now are being used even in haemopoietic stem cells transplantation. The present study was planned with an objective to study the complications, safety and efficacy of PICCs in haemopoietic stem cell transplantation for haematological diseases. Methods: A prospective cohort study was conducted in stem cell transplantation department of our tertiary care cancer hospital for a period of two and half years as per the proforma. All patients with hematological cancer who were undergoing stem cell transplantation were enrolled and were followed up until catheter removal or patient death. The basic information was recorded at the time of PICC insertion, weekly care, and removal after the transplantation. The data were analyzed to study the aims and objectives of the study. Results: Seventy two PICCs were inserted over a period of two and half years for a total of 8048 catheter-days (mean of 111.77 +/_ 66.55 days i.e 3.7 months, range: 9 to 269 days). Out of these 72 PICCs, 11 (15.27%) PICCs had complications and all of them were removed at the rate of 1.35/1000 PICC-days. Catheter related blood stream infection (CRBSI) was higher in allogenic transplant group (16%) than in autologous group (2.5%) while thrombosis was present in allogenic group only. Mortality due to non-PICC complications was higher in allogenic transplant (40%) than in the autologous group (7.5%). Conclusion: PICCs plays an integral part to supportive care in hematopoietic stem cell transplantation for hematological cancers.